THE EFFECT OF TRANSFORMATIONAL LEADERSHIP DIMENSION ON EMPLOYEE PERFORMANCE AT PT. KALIMANTAN SAWIT KUSUMA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
A substantial corpus of research has examined the impact of transformational leadership, yet studies on each dimension of transformational leadership remain scarce. This research aims to address this gap by examining the influence of four dimensions of transformational leadership, with a particular focus on their impact on employee performance in palm oil companies in Indonesia. This research employs a descriptive quantitative methodology with a survey method. Furthermore, the data collected in the field was obtained through the distribution of questionnaires to 100 employees in hard copy form. Following this, the data will be analyzed using SEM PLS 3.2.9. The findings indicate that the three dimensions of transformational leadership have a significant positive effect on employee performance, with only idealistic influence exhibiting no significant effect. The survey was conducted exclusively on employees who were based in the office, with those working in the field being excluded. Nevertheless, this research provides theoretical implications in the form of empirical evidence of the influence of transformational leadership dimensions on employee performance in the context of human resources working in palm oil companies in Indonesia. Furthermore, the findings provide practical implications with recommendations for improving employee performance.
Keywords: Intellectual Stimulation; Idealised Influence; Inspirational Motivation; Individualized Consideration; Employee Performance.